The Current State of the Accounting Reform in Russia: the Results of 2017 - Aleksei E. Ivanov (Учёт. Анализ. Аудит)
Introduction. The article deals with the current state of the accounting reform in the Russian Federation. This reform significantly accelerated in 2016-2017. Particular attention is paid to highlighting the opportunities for anyone interested in the development of Russian accounting to participate in the elaboration of accounting regulation documents. Methods. For the research, I used the methods of analysis, synthesis and comparison. The Russian Accounting Standards and their Drafts, International Financial Reporting Standards, Industry Accounting Standards and their Drafts, Accounting Recommendations and information from the Russian Federation Ministry of Finance and subjects of non-state accounting regulation are the research source data. Results. I concluded that since 2016 a qualitatively new level of Russian accounting reform has been observed. This level is characterized by a broad involvement of non-state accounting regulation subjects to the development of accounting regulation documents. I have defined the circle of drafts developers of this documents and the scope of their norm-setting activities. I have described the rules for the interaction between non-state accounting regulation subjects with the Ministry of Finance of the Russian Federation and other interested parties in the development of federal accounting standards. I have summed up the preliminary results of the work of state and non-state accounting regulation subjects as of the end of 2017. Discussion. The results of the research could prove to be useful to the representatives of the professional community (including university employees) who plan to participate in the public discussion of draft federal accounting standards as well as developing accounting recommendations.